AN APPROACH TO THE ENANTIOSPECIFIC SYNTHESES OF SESBANIMIDE AND ITS ENANTIOMER FROM D-GLUCOSE - Fleet, G; Shing, T (1984)
An approach to the enantiospecific syntheses of sesbanimide and its enantiomer is described; enantiomeric intermediates in the syntheses of both compounds possessing the required glutarimide and 1,3-dioxane rings are derived from D-glucose.